Catecholamine effects on human melanoma cells evoked by α1-adrenoceptors - Scarparo, Ana Cristina; Sumida, Doris Hissako [UNESP]; Patrão, Marília T. C. C.; Avellar, Maria Christina W.; Visconti, Maria Aparecida; Castrucci, Ana Maria de Lauro (Springer Nature, 2004)
The biological effects of catecholamines in mammalian pigment cells are poorly understood. Our previous results showed the presence of α1-adrenoceptors in SK-Mel 23 human melanoma cells. The aims of this work were to (1) characterize catecholamine effects on proliferation, tyrosinase activity and expression, (2) identify the α1- adrenoceptor subtypes, and (3) verify whether chronic norepinephrine (NE) treatment modified the types and/or pharmacological characteristics of adrenoceptors present in SK-Mel 23 human melanoma cells. Cells treated with the aradrenergic agonist, phenylephrine (PHE, 10-5 or 10-4 M), for 24-72 h, exhibited decreased cell proliferation and enhanced tyrosinase activity, but unaltered tyrosinase expression as compared with the control. The proliferation and tyrosinase activity responses were inhibited by the α1-adrenergic antagonist prazosin, suggesting they were evoked by α1-adrenoceptors. The presence of actinomycin D, a transcription inhibitor, did not diminish PHE-induced effects. RT-PCR assays, followed by cloning and sequencing, demonstrated the presence of α1A- and α1B-adrenoceptor subtypes. NE-treated cells (24 or 72 h) were used in competition assays, and showed no significant change in the competition curves of α1-adrenoceptors as compared with control curves. Other adrenoceptor subtypes were not identified in these cells, and NE pretreatment did not induce their expression. In conclusion, the activation of SK-Mel 23 human melanoma α1- radrenoceptors elicit biological effects, such as proliferation decrease and tyrosinase activity increase. Desensitization or expression of other adrenoceptor subtypes after chronic NE treatment were not observed.
Keywords: α1-Adrenoceptors; Catecholamines; Cell proliferation; SK-Mel 23 melanoma cells; Tyrosinase activity; alpha 1 adrenergic receptor; alpha 1 adrenergic receptor blocking agent; alpha 1 adrenergic receptor stimulating agent; ascorbic acid; benoxathian; catecholamine; dactinomycin; monophenol monooxygenase; noradrenalin; phenylephrine; prazosin; adrenergic system; catecholamine metabolism; cell proliferation; cell strain SK Mel 23; controlled study; enzyme activity; human; human cell; melanoma cell; pigment cell; priority journal; reverse transcription polymerase chain reaction; Western blotting; Adrenergic alpha-Agonists; Binding, Competitive; Cell Division; Cell Line, Tumor; Gene Expression; Humans; Melanoma; Monophenol Monooxygenase; Norepinephrine; Phenylephrine; Receptors, Adrenergic, alpha-1; Skin Neoplasms